Habitat International - Habitat International (Elsevier, 2026)
Habitat International is dedicated to the study of urban and rural human settlements: their planning, design, production and management. Its main focus is on urbanisation in its broadest sense in the developing world. However, increasingly the interrelationships and linkages between cities and towns in the developing and developed worlds are becoming apparent and solutions to the problems that result are urgently required. The economic, social, technological and political systems of the world are intertwined and changes in one region almost always affect other regions. Habitat International welcomes reports of research on urban issues such as policy and implementation, the links between planning, building and land, finance and management, urban design, the interaction between the natural environment and urban areas the provision of urban services and other related problems.
FI 1.67
Q1
Keywords: Earth; Space & Environmental Sciences; Acuerdos transformativos; Transformative agreements; Asentamientos humanos urbanos y rurales; Urbanización, políticas urbanas y gestión de servicios urbanos; Planificación, diseño urbano y vínculos entre entorno natural y áreas urbanas